Adaptive Feedback Control for Synchronization of Chaotic Neural Systems with Parameter Mismatches. (9th September 2018) - Ye, Qian; Jiang, Zhengxian; Chen, Tiane
Abstract : This work pertains to the study of the synchronization problem of a class of coupled chaotic neural systems with parameter mismatches. By means of an invariance principle, a rigorous adaptive feedback method is explored for synchronization of a class of coupled chaotic delayed neural systems in the presence of parameter mismatches. Finally, the performance is illustrated with simulations in a two-order neural systems.